The bang for the birr: Public expenditures and rural welfare in Ethiopia - Mogues, Tewodaj; Ayele, Gezahegn; Paulos, Zelekawork (International Food Policy Research Institute, 2008)
During the past decade and a half, Ethiopia’s approach to promoting development and improving the lives of the country’s rural population has been driven by a government strategy called Agricultural Development–Led Industrialization (ADLI). This strategy’s main goal is to encourage fast, broad-based development within the agricultural sector in order to power economic growth. While ADLI considers regulatory, trade, market, and other policies to be key engines of agricultural growth, it also focuses on increasing public expenditure in agriculture and road infrastructure, as well as in social sectors that are perceived as contributing to agricultural productivity. Thus, Ethiopia’s public expenditure policy is at the heart of the policy measures emerging from ADLI. Given budget constraints, it is essential to examine the relative contributions that different types of public investments make to welfare. An improved understanding of investment outcomes will have important implications for expenditure policy, especially in terms of the portfolio composition of public resources. This research report explores and compares the impacts of different types of public spending on rural household welfare in Ethiopia. Most previous studies examining the link between public expenditure and development outcomes either explore how the size of overall public expenditure or public investment affects growth or poverty, or they correlate spending in one economic sector with outcomes in that sector or with broader measures of welfare. Both types of studies can provide useful input into policymaking decisions. However, there is a striking lack of research aimed at examining how the composition of public spending affects key development outcomes—a particularly policy-relevant question. This study fills that gap. It compares the impact of different types of public spending through a three-stage analysis. The first stage assesses the impact of access to different sector-specific services on rural household consumption and the productivity of households’ private assets, differentiating these effects by geographic region. The second stage determines the contribution of different types of public spending to key sector-specific outcomes. The final stage of the analysis draws on the first two to estimate the effect on rural welfare of a unit increase in public spending across different sectors.